2014
DOI: 10.2134/agronj13.0474
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelates Alleviate Iron Chlorosis in Soybean on High pH Soils

Abstract: High pH soils frequently lead to iron deficiency chlorosis (IDC) in soybean [Glycine max (L.) Merr.]. As a result, yields for soybean are often reduced. Studies in the north-central United States have shown improvements in grain yield after applying Fe chelates on calcareous soils, but this practice has not been evaluated in a southern climate. Two sites within the Blackbelt region of Alabama were evaluated for response to Fe-EDDHA, Fe-Citrate, and FeSO 4 for their effect on yield and chlorosis in 2010, 2011, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…Gamble et al. (2014) found a soybean yield increase of 2.98 bu/ac across a multiyear study at two high‐pH sites in Alabama. Foliar sprays containing iron salts or chelates are effective at correcting plant iron deficiencies during the growing season, but they may require repeated applications to prevent reoccurrence of deficiency.…”
Section: R Management Of Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamble et al. (2014) found a soybean yield increase of 2.98 bu/ac across a multiyear study at two high‐pH sites in Alabama. Foliar sprays containing iron salts or chelates are effective at correcting plant iron deficiencies during the growing season, but they may require repeated applications to prevent reoccurrence of deficiency.…”
Section: R Management Of Ironmentioning
confidence: 99%
“…Iron fertilizers protected with an organic chelate can be effectively applied to soils to correct plant deficiencies. Chelated fertilizers such as Fe‐EDDHA (Kaiser et al., 2014; Gamble et al., 2014) have been used with reasonable effectiveness, but their cost may be prohibitive for whole‐field applications. Gamble et al.…”
Section: R Management Of Ironmentioning
confidence: 99%
“…Iron fertilizers protected with an organic chelate can be effectively applied to soils to correct plant deficiencies. Chelated fertilizers such as Fe-EDDHA (Kaiser et al, 2014;Gamble et al, 2014) have been used with reasonable effectiveness, but their cost may be prohibitive for whole-field applications. Gamble et al (2014) found a soybean yield increase Iron deficiency in maize.…”
Section: R Management Of Ironmentioning
confidence: 99%
“…Products combating IDC are often applied as in-furrow applications or foliar sprays as demonstrated by Gamble et al [12] in a soybean study in Alabama, USA. Visual chlorosis scores were lowered (less IDC) for in-furrow application and foliar spray, but in-furrow application resulted in the most IDC reduction although both methods provided similar yield [12].…”
Section: Introductionmentioning
confidence: 99%